The crossﬂow piezo-electrooptic effect in crystals. Example of lithium tantalate - Andrushchak, A.S.; Sydoryk, I.V.; Kaidan, M.V.; Vlokh, R.O. (Condensed Matter Physics, 2000)
In the present paper the thermodynamic and phenomenological descriptions of the crossﬂow piezo-electrooptic effect in crystals have been made. For example the necessary experimental measurements of this effect have been carried out in the lithium tantalate crystals. For these crystals at ﬁrst the P₃₃₁₁₃ - P₁₁₁₁₃ = −4, 6 • 10⁻¹⁹ m³/ N•V absolute coefﬁcients difference of crossﬂow piezo-electrooptic effect were determined by two measurement methods. У даній роботі було здійснено термодинамічний і феноменологічний описи перехресного п’єзо-електрооптичного ефекту в кристалах. Для прикладу були проведені необхідні експериментальні вимірювання вказаного ефекту в кристалах танталату літію. Для цих кристалів на основі двох різних методів вимірювання вперше було визначено різницю абсолютних коефіцієнтів перехресного п’єзо-електрооптичного ефекту P₃₃₁₁₃ - P₁₁₁₁₃ = −4, 6 · 10⁻¹⁹ м³/ Н·В.